Sports and substance use in high school students: different perspectives of this relationship - Bedendo, André; Andrade, André Luiz Monezi; Noto, Ana Regina (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2015)
The aim of this study was to describe the relationship between playing sports and substance use in high school, students. A search was conducted, without restrictions by date, in the main health databases saúde (Cochrane, LILACS, PsycINFO, PubMed, SciELO and Scopus). Analysis showed that playing sports can be both a risk and a protection factor concerning substance use, depending on a series of variables. Among these the following stand out: gender, type of sport, socio-cultural environment and motivation, both to play sport and to take the substance. Planning preventative actions that involve sport should consider the various factors involved, so as to encourage prevention of drug consumption among adolescents.